Sevoflurane Preconditioning Rescues PKMζ Gene Expression from Broad Hypoxia-Induced mRNA Downregulation Correlating with Improved Neuronal Recovery - Joan Y. Hou; Kim D. Allen; A. Iván Hernandez; James E. Cottrell; Ira S. Kass (NeuroSci)
Hypoxia due to stroke is a major cause of neuronal damage, leading to loss of cognition and other brain functions. Sevoflurane preconditioning improves recovery after hypoxia. Hypoxia interferes with protein expression at the translational level; however, its effect on mRNA levels for neuronal protein kinase and anti-apoptotic genes is unclear. To investigate the link between sevoflurane preconditioning and gene expression, hippocampal slices were treated with 4% sevoflurane for 15 min, a 5 min washout, 10 min of hypoxia, and 60 min of recovery. We used quantitative PCR to measure mRNA levels in the CA1 region of rat hippocampi. The mRNA levels for specific critical proteins were examined, as follows: Protein kinases, PKCγ (0.22), PKCε (0.38), and PKMζ (0.55) mRNAs, and anti-apoptotic, bcl-2 (0.44) and bcl-xl (0.41), were reduced 60 min after hypoxia relative to their expression in tissue not subjected to hypoxia (set to 1.0). Sevoflurane preconditioning prevented the reduction in PKMζ (0.88 vs. 1.0) mRNA levels after hypoxia. Pro-apoptotic BAD mRNA was not significantly changed after hypoxia, even with sevoflurane preconditioning (hypoxia 0.81, sevo hypoxia 0.84 vs. normoxia 1.0). However, BAD mRNA was increased by sevoflurane in non-hypoxic conditions (1.48 vs. 1.0), which may partially explain the deleterious effects of volatile anesthetics under certain conditions. The DNA repair enzyme poly ADP-ribose polymerase 1 (PARP-1) was increased by sevoflurane in tissue not subjected to hypoxia (1.23). PARP-1 mRNA was reduced in untreated tissue after hypoxia (0.21 vs. 1.0); sevoflurane did not improve PARP-1 after hypoxia (0.27). Interestingly, the mRNA level of the cognitive kinase PKMζ, a kinase essential for learning and memory, was the only one protected against hypoxic downregulation by sevoflurane preconditioning. These findings correlate with previous studies that found that sevoflurane-induced improvement of neuronal survival after hypoxia was dependent on PKMζ. Maintaining mRNA levels for critical proteins may provide an important mechanism for preserving neuronal function after stroke.